PEARSON CORRELATION ANALYSIS OF OIL TESTING PARAMETERS ON REMAINING USEFUL LIFE (RUL) IN GEARBOX CHAIN BUCKET ELEVATOR - Rahma Wati; Desmarita Leni; Muchlisinalahuddin Muchlisinalahuddin; Dytchia Septi Kesuma (International Journal of Multidisciplinary Research and Literature, 2026)
The gearbox in a chain bucket elevator system is a critical component of the cement production process and relies heavily on the reliability of the lubrication system. As operating hours increase, lubricating oil quality degrades, potentially affecting its remaining useful life (RUL). This study aims to analyse the linear relationship between oil-test result parameters and Remaining Useful Life (RUL) for chain bucket elevator gearboxes using the Pearson correlation method. The data used are 50 laboratory test results for the gearbox oil chain bucket elevator at Cement Mill Indarung VI, PT. Semen Padang collected from June 2019 to October 2025. The oil testing parameters analysed include DV Visc 40°C, DV Visc (%), ISO >6, NAS, Contamination Index, Ferrous Index, Chemical Index, Dielectric, and % Water. Data were analysed using the Pearson correlation method and visualised as a heatmap. The analysis results showed that the viscosity parameter had the strongest negative correlation with RUL, with a value of -0.741 for DV Visc 40°C and -0.658 for DV Visc (%). The Contamination Index and % Water parameters also showed a negative correlation with RUL, albeit with a lower level of influence. In practice, the results of this study can serve as a basis for oil condition monitoring to support condition-based maintenance strategies, enabling more timely oil change decisions and minimising the potential for gearbox failure.